Impactos na coordenação de relés com elementos 51P, 51Q E 51G em rede de distribuição de média tensão devido à conexão de parque eólico DFIG com diferentes níveis de potência - Galindo, Martins Dario Gonçalves (2024)
This paper presents the evolution of wind turbine generators, the regulations regarding fault ride-through or low voltage ride-through, the main types of wind turbine generators, and the characteristics of their short-circuit currents, which differ from those of synchronous generators. In more detail, it presents the DFIG wind turbine generator, which injects balanced short-circuit currents even during asymmetric short-circuits into the distribution network due to the adopted control strategy of the back-to-back convert. Then, the CIGRE distribution network is modeled and validated in the electromagnetic transient program PS SIMUL as well as the time-overcurrent relays with the phase element 51P, negative sequence element 51Q, and zero sequence element 51G, to verify the relays’ impact when the different penetration levels of the DFIG wind turbine generator generic model is connected to the distribution network. The analysis is made during system operation and short circuits on the buses. Only the phase elements of the relays that observe the contributions of the short-circuit currents from the wind turbine generator in an opposite direction when the wind turbine generator is not connected lose coordination. The solution for this is the addition of the directional phase element 67P. The negative and zero sequence elements of all the relays analyzed do not need to be adjusted independently of the power level of the DFIG wind turbine generator due to the suppression of the negative and zero sequence currents, even during asymmetric short circuits. Regarding the trip times of the relay elements, there are no considerable time variations as the wind turbine generator power increases.